Thrombocytosis and portal vein thrombosis after splenectomy for paediatric haemolytic disorders: How should they be managed?. (23rd September 2018) - Stringer, Mark D; Lucas, Nathanael
Abstract: Splenectomy is indicated in selected children with haemolytic anaemia. Postoperatively, thrombocytosis occurs in at least 80% and is one of the factors implicated in the development of acute portal venous thrombosis after splenectomy in adults. A literature review shows that children are also at risk of this complication, but the incidence is low. The risk is greatest in those with particularly large spleens. Laparoscopic splenectomy does not reduce the risk of this complication. Early detection and anticoagulation usually leads to successful resolution of the thrombosis and can mitigate the risk of developing cavernous transformation of the portal vein and chronic portal hypertension. Any child with severe or unexplained postoperative abdominal pain, fever and/or vomiting after splenectomy demands urgent abdominal imaging to exclude this complication. In asymptomatic individuals, a routine Doppler ultrasound scan 1 week postoperatively is advisable if they had a particularly large spleen, longer than usual duration of surgery and/or have a marked postoperative thrombocytosis. There is no evidence for routine administration of antiplatelet drugs and/or subcutaneous heparin prophylaxis in children after splenectomy, including those who develop postoperative thrombocytosis, but children with particularly large spleens may be a subset that benefit.